Form over Substance: The Board Governance Practices in Indonesia - Nureni Wijayati (The Indonesian Journal of Accounting Research, 2022)
The study aims at investigating the decoupling behavior wherein firms tend to only adopt written policies formally, while they avoid implementing internal corporate governance mechanisms substantively. The analysis is focused on the area of the Board's responsibility. The sample consists of 487 firm-year observations having the ASEAN Corporate Governance Scorecard (ACGS) for the period 2013-2017. Using institutional theory, the research finds that fifty-seven percent (279 out of 487 observations) in the sample show decoupling behavior. Decoupling behavior is more pronounced in large firms with lower performance and higher leverage. Furthermore, the financial (banking) industry is less likely to behave decoupling due to the nature of the industry is highly regulated and enforced.